Analisis Sistem Antrian di Plasa Telkom Solo dengan Metode Simulasi - Eko Liquiddanu; Wakhid Ahmad Jauhari; Yaning Tri Hapsari (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2009)
Plasa Telkom Solo is a service place belonging to Telkom which is provided to serve Telkom customer with nine service servers. Those nine services servers can handle new setting and mutation, complains, information, and cash payment and non cash payment. Queue in the scale of customer service is important to be considered because the long queue will make the customer uncomfortable. The queue happens because the need of service is bigger than the capacity of service. Therefore, the customer cannot be served immediately because the busy service. This research is conducted to analyze the queue system to find the best number of the server and service system in Plasa Telkom Solo. This research uses simulation method to find the best solution for the company to decide the number of the servers. Thesimulation model is used because this model can give solution if analytic model is failed to do that. Analytic model cannot be used in this research since in Plasa Telkom Solo there are four kinds of service with different approximate time service.Based on the research, the best numbers of server is seven. Meanwhile, the service system model are combining service 1 (new setting and mutation) and service 2 (complain) with the number of server 5 and service 3 (information) combines with service 4 (cash payment and non cash payment) with number of server is 2. This model can reduce the queue time for 21,7325 minutes (before the simulation) to be 17,8694 minutes (after simulation). The time difference is 3.8631 minutes with utilization 0,8996 (89,96%) or 458,796 minutes (7,65 hours) per day and the free time for the server is 0,1004 (10,04%) atau 51,2040 minutes (0,85 hours) per day, in which per day there is 8,5 work time.